University teaching development workshops as sites of joint decision-making: Negotiations of authority in academic cultures. (February 2023) - Ripatti-Torniainen, Leena; Stevanovic, Melisa
Abstract: This study analyzed interactional practices in the strategic development of teaching at a research university in Finland. Drawing on a novel combination of conversation analysis and cultural discourse analysis, the study investigated how participants negotiate decision-making power and authority when developing new interdisciplinary teaching in workshop groups. Specific attention was paid to the participants' ways of making and responding to each other's proposals and invoking disciplinary and pedagogical knowledge as a basis for steering joint decision-making interaction. The study made use of the distinction between epistemic authority (i.e., expertise in a field of knowledge) and deontic authority (i.e., power to determine action), as well as the notion of academic cultures. The study identified three different academic cultures of negotiating authority, each associated with a workshop group: the collegial, developmental, and managerial cultures. Furthermore, the study showed that both disciplinary and pedagogical mastery can occasionally prevent inclusive dialogue that plays an elementary role in enabling joint decision-making in the development of teaching at universities.